2017
DOI: 10.1111/jfb.13296
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure and comparative diversity of smallmouth bass Micropterus dolomieu: congruent patterns from two genomes

Abstract: Genetic diversity and divergence patterns of smallmouth bass Micropterus dolomieu spawning groups are analysed across its northern native range with mtDNA cytochrome b gene sequences and eight unlinked nuclear DNA microsatellite loci. Results reveal high levels of genetic variability and significant differences in allelic representation among populations (mtDNA: mean ± s.e., H = 0·50 ± 0·06, mean ± s.e., θ = 0·41 ± 0·02 and microsatellites: mean ± s.e. H = 0·46 ± 0·03, mean ± s.e. θ = 0·25 ± 0·01). The distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 95 publications
(176 reference statements)
0
7
0
Order By: Relevance
“…Moreover, the selection of loci with high PIC for the analysis can also lead to high genetic diversity. Microsatellite markers have demonstrated to be highly sensitive for detecting the population structure of fish (Cheng et al 2015;Stepien et al 2017;. In this study, analyses based on seven microsatellite loci revealed low levels of genetic differentiation for P. argenteus.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Moreover, the selection of loci with high PIC for the analysis can also lead to high genetic diversity. Microsatellite markers have demonstrated to be highly sensitive for detecting the population structure of fish (Cheng et al 2015;Stepien et al 2017;. In this study, analyses based on seven microsatellite loci revealed low levels of genetic differentiation for P. argenteus.…”
Section: Discussionmentioning
confidence: 78%
“…Microsatellites (simple sequence repeats, SSRs) are tandemly repeated motifs of 1-6 bases characterized by a high degree of length polymorphism (Zane et al 2002), and they are sensitive indicators of population genetic structure (Cheng et al 2015;Song et al 2016;Stepien et al 2017). In previous studies, we evaluated the phylogeographical structure of P. argenteus by mitochondrial DNA markers, and two lineages were obtained (Li et al 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the population genetic structure of natural populations of wildlife species provides essential information for the development of conservation and management strategies (Nakagawa et al, 2016;Stepien et al, 2017). The survival of a species or population depends on its ability to adapt to environmental changes by its genetic variation and thus genetic variation is essential for long-term survival and evolution (Bataillon et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite markers have demonstrated to be highly sensitive for detecting the population structure of fish (Cheng et al 2015; Stepien et al 2017; Li et al 2018). In this study, analyses based on seven microsatellite loci revealed low levels of genetic differentiation for P.argenteus .…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellites (simple sequence repeats, SSRs) are tandemly repeated motifs of 1–6 bases characterized by a high degree of length polymorphism (Zane et al 2002), and they are sensitive indicators of population genetic structure (Cheng et al 2015; Song et al 2016; Stepien et al 2017). In previous studies, we evaluated the phylogeographical structure of P.argenteus by mitochondrial DNA markers, and two lineages were obtained (Li et al 2017b).…”
Section: Introductionmentioning
confidence: 99%